A platform-agnostic, function first-based antibody discovery strategy using plasmid-free mammalian expression of antibodies. Issue 1 (1st January 2021) - Zhang, Ruijun; Prabakaran, Ponraj; Yu, Xiaocong; Mackness, Brian C.; Boudanova, Ekaterina; Hopke, Joern; Sancho, Jose; Saleh, Jacqueline; Cho, HyunSuk; Zhang, Ningning; Simonds-Mannes, Helene; Stimple, Samuel D.; et al.
ABSTRACT: Hybridoma technology has been valuable in the development of therapeutic antibodies. More recently, antigen-specific B-cell selection and display technologies are also gaining importance. A major limitation of these approaches used for antibody discovery is the extensive process of cloning and expression involved in transitioning from antibody identification to validating the function, which compromises the throughput of antibody discovery. In this study, we describe a process to identify and rapidly re-format and express antibodies for functional characterization. We used two different approaches to isolate antibodies to five different targets: 1) flow cytometry to identify antigen-specific single B cells from the spleen of immunized human immunoglobulin transgenic mice; and 2) panning of phage libraries. PCR amplification allowed recovery of paired VH and VL sequences from 79% to 96% of antigen-specific B cells. All cognate VH and VL transcripts were formatted into transcription and translation compatible linear DNA expression cassettes (LEC) encoding whole IgG or Fab. Between 92% and 100% of paired VH and VL transcripts could be converted to LECs, and nearly 100% of them expressed as antibodies when transfected into Expi293F cells. The concentration of IgG in the cell culture supernatants ranged from 0.05 µg/ml to 145.8 µg/ml (mean = 18.4 µg/ml). Antigen-specific binding was displayed by 78–100% of antibodies. High throughput functional screening allowed the rapid identification of several functional antibodies. In summary, we describe a plasmid-free system for cloning and expressing antibodies isolated by different approaches, in any format of choice for deep functional screening that can be applied in any research setting during antibody discovery.